The Impact of Energy Use on Indonesian Economic Development: A Qualitative Analysis of Stakeholder Views and Attitudes - Tohiroh Tohiroh; Aep Saefullah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to determine the effect of energy consumption on economic growth in Indonesia, as well as to investigate stakeholder perceptions and attitudes regarding energy consumption and its impact on economic growth. The research method employed is a descriptive qualitative approach based on literature, observation, and media studies involving stakeholders including government officials, experts, academics, and the general people. The study's findings indicate that increased domestic energy use can boost economic growth. Increased energy consumption promotes the expansion of home economic industries. Second, stakeholders have diverse perceptions and attitudes regarding energy usage and its impact on economic growth. Some stakeholders think that energy consumption is vital for economic progress, while others claim that excessive energy consumption has a negative impact on environmental and economic sustainability. The importance of collaborating with all stakeholders to promote energy consumption and Indonesian economic growth. The study focuses on stakeholder views of energy usage, which has an impact on economic growth. The study suggests that more research on energy usage should be conducted in order to broaden and fully improve economic growth. This research also assists to offering insights and true pictures of stakeholders regarding the conditions of energy use and economic growth.